Cutaneous stimulation of slow stroke back massage to reduce the pain of sectio caesarea - Ningrum, Ema Wahyu; Novitasari, Dwi; Murniati, Murniati (Universitas Muhammadiyah Purwokerto, 2019)
Background: Labor with sectio caesarea may result to an impact after surgery, namely pain. The pain reduction technique that can be done is cutaneous stimulation of Slow Stroke Back Massage.Objective: This study aims to determine cutaneous stimulation of Slow Stroke Back Massage towards pain in post sectio caesarean patientsMethods: This study used Pre Experimental Design with the One-Group Pretest-Posttest Design approach. The samples studied were 20 patients of post SC surgery by consecutive sampling technique. The instrument used a VAS scale observation sheet. The research data were analyzed through Wilcoxon test.Results: The results showed that the average pain intensity before the intervention was 6.10, the average intensity of pain after the intervention implemented reached 3.90, there was a difference of pain intensity in post sectio caesarean patients before and after cutaneous stimulation technique of Slow Stroke Back Massage (p-value = 0.001)Conclusion: there is an effect of cutaneous stimulation of Slow Stroke Back Massage on pain in post sectio caesarean patients.